The Channel Analysis and Marketing Efficiency Lada in Moramo District South Konawe Regency - Amurwani, Sulistyo; Rianse, Ilma Sarimustaqiyma; Sadimantara, Fahria Nadiryati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
This research aims to know the pepper marketing channels, the marketing margins, and the efficiency of each marketing channel. This research was conducted in the Moramo District of South Konawe Regency from May to November 2021. The study was analyzed using descriptive analysis, marketing margin analysis, and marketing efficiency (Farmer's Share). The sample of pepper farmers was 66 people. In comparison, the sample of marketing agencies was determined by the Snowball Sampling method, which amounted to 6 collectors and small traders as many as three people, and large traders as many as one person. The study results showed the existing channel marketing: (a) Producer, Collector, Trade significant, Consumers (b) Producers, Traders small, Traders big, Consumers. Performance of the pepper marketing channel in channel I, namely the marketing margin of IDR1.000/kg and IDR3,500/kg with a marketing profit of IDR925.52/kg and IDR3.293.56/kg, while in channel II the marketing margin is IDR1.500/kg and IDR2.000/kg with marketing profits of IDR1.337.39/kg and IDR1.793.56/kg. The results of the analysis showed that the percentage of the share of prices received by producers (Farmer's Share) from both pepper marketing channels each showed above 50% in marketing channel I by 92% and marketing channel II by 94%, this indicates that both marketing channels are already very efficient. However, from the farmer's point of view, marketing channel II is more efficient because the profits obtained by farmers are more than in marketing channel I.